“Study in the Mountain” – the Influence of the Mountain Environment on Certain Mental Components and Students' Academic Performance During Sessions - Yordanov, Ventsislav; Yordanov, Evgeni (Research Papers, 2017)
The goal of the present study is to sound out the impact of the mountain background over UNWE student’s behavior through the period of the project, that we called “Learn in the Mountain”. 44 students took part in the survey. 24 of them did mountain hiking in the time of their university session and another 20 students were in as part of a control group. Object of our study were some psychological components of the students behavior and their academic grades.Results shows that the students, who did hiking, demonstrate statistically significant decrease in their academic burnout and their negative emotions in the end of the exam period. From the other side the other group of 20 students indicate self-esteem reduction and lower level of optimism.
Keywords: Mountain; Studying; Academic performance; Mental components